Development of digital food photographs as a tool to visually estimate food portion size in multi-ethnic Malaysian adult - Mohd Razif, Shahril; Abbe Maleyki, Mhd.Jalil; Marhazlina, Mohamad; Wee, Bee Suan; Sakinah, Harith; Engku Fadzli Hasan, Syed Abdullah; Laila Ruwaida, Mohd Zainuddin (2019)
Background/Alms: Unreliable food portion size estimation is one of the causes of under reporting in dietary surveys. Digital food photograph is a set of photograph series depicting different amounts of food that can be used to describe portion sizes. This study aimed to develop digital food photographs for multi-ethnic Malaysian adults and discuss its usage, advantages, and limita-tions. Methods: A total of 244 commonly consumed foods in Ma-laysia that were recognized by a local nutritional survey, market survey, and interviewing nutrition experts. were used in the study. In obtaining food items, certain dishes were prepared according to a standard recipe book, while other items were purchased from recognized restaurants and local markets. White crockery on with white background was used to present the food items and they were photographed using a camera setup recommended for food photography. Three types of digital photographs were used to show the food items i.e. serial (71%), range (25%), and guide (4%). Results: Three types of digital photographs were used to show the food items i.e. serial (71%), range (25%), and guide (4%). Mainly all digital photographs of foods (n = 217) were captured using a camera placed at an angle of 42° to represent the view of a person of average height, sitting at a table, and looking at a plate on the table in front of him/her. The liquid portion series (n = 27) were photographed at an angle of 90° to get life-size images. Conclusion: Digital food photographs could be a valuable resources for development of electronic dietary assessment tools in Malaysia as well as in other South East Asian countries where similar foods are consumed.